Prevalence of vitamin D deficiency and the effect of anthropometric and lifestyle factors on vitamin D status in healthy women residing in Riyadh - Binobead, Manal Abdulaziz; Al-Qahtani, Wahidah Hazzaa; Al Bader, Nawal Abdullah; AlSedairy, Sahar Abdulaziz; Arzoo, Shaista (Progress in Nutrition, 2019)
Objective: Hypovitaminosis D is a global health issue, and its increasing prevalence affects people of all ages. This study aimed to determine the vitamin D statuses of healthy women residing in Riyadh, based on measured serum calcidiol (25(OH)2D3) levels and to assess the effects of demographic, anthropometric, and lifestyle factors on vitamin D status. Method: A structured questionnaire was designed and completed after patient consent acquisition to obtain demographic, anthropometric, and lifestyle information. A food frequency questionnaire was used to assess dietary intake, and an immunoassay was used to determine serum vitamin D levels. Result: The mean age of the participants was 33.46 years, and approximately 56% of the participants reported no exposure to sunlight. Only 26.98% of the participants had a normal body mass index (BMI), and 42.86% of the participants had a waist circumference